Pengaruh Lingkungan Bisnis Terhadap Strategi Partnership Bank Perkreditan Rakyat - Ucu Supriatna; Agus Rahayu; Lili Adibowo (Universitas Pendidikan Indonesia, 2022)
AbstractThis study is useful to determine the effect of workload and work environment on the performance of employees of PT. This research is motivated by the phenomenon that competition between financial institutions is getting tighter, especially banking institutions. This competition is felt by Rural Banks (BPR) which is more specialized in micro, medium, and small businesses in West Java, so it is necessary to implement a strategy for maintaining BPR's performance still well. The implementation of a partnership strategy is one way that must be done to speed up time in business development. To implement the partnership strategy, BPR has to see what is the important indicator from the external and internal environmental businesses that have an influence. The population taken in this study is Rural Banks operating in West Java Province with as many as 237 offices. Sampling was done by proportional random sampling technique. The sample size of 149 is arranged proportionally according to the distribution in each Regency or City. The respondents are the President Director of each BPR, who understands the industry, competitive environment, partnership strategy, and performance. By using Structural Equation Modeling (SEM) the results show that the external environment and the internal environment have a positive and significant effect on the partnership strategy variable with a coefficient of determination R Square 94.8%. The external environment partially has a positive and significant effect on the partnership strategy by 40.3%, the most dominant indicator being competitors. The internal environment partially has a positive and significant effect on the partnership strategy with 21.3% the most dominant indicator of shareholder capability.Keywords: external environmental; internal environmental; the partnership strategy. AbstrakPenelitian ini dilatarbelakangi oleh fenomena persaingan antar lembaga keuangan yang semakin ketat, khususnya lembaga perbankan. Persaingan ini dirasakan oleh Bank Perkreditan Rakyat (BPR) yang lebih mengkhususkan pada usaha mikro, menengah, dan kecil di Jawa Barat, sehingga perlu diterapkan strategi untuk menjaga kinerja BPR tetap baik. Penerapan strategi kemitraan merupakan salah satu cara yang harus dilakukan untuk mempercepat waktu dalam pengembangan usaha. Untuk menerapkan strategi kemitraan, BPR harus melihat apa indikator penting dari lingkungan eksternal dan internal bisnis yang berpengaruh. Populasi yang diambil dalam penelitian ini adalah Bank Perkreditan Rakyat yang beroperasi di Provinsi Jawa Barat yang berjumlah 237 kantor. Pengambilan sampel dilakukan dengan teknik proportional random sampling. Besar sampel sebanyak 149 orang disusun secara proporsional menurut sebaran di masing-masing Kabupaten atau Kota. Respondennya adalah Direktur Utama masing-masing BPR, yang memahami industri, lingkungan persaingan, strategi kemitraan, dan kinerja. Dengan menggunakan Structural Equation Modeling (SEM) diperoleh hasil bahwa lingkungan eksternal dan lingkungan internal berpengaruh positif dan signifikan terhadap variabel strategi kemitraan dengan koefisien determinasi R Square 94,8%. Lingkungan eksternal secara parsial berpengaruh positif dan signifikan terhadap strategi kemitraan sebesar 40,3%, indikator yang paling dominan adalah pesaing. Lingkungan internal secara parsial berpengaruh positif dan signifikan terhadap strategi kemitraan dengan 21,3% indikator kapabilitas pemegang saham yang paling dominan. Kata kunci: lingkungan eksternal; lingkungan internal; strategi kemitraan